Karakterisasi Fitokimia dan Uji Daya Hambat Senyawa Daun Kelakai (stenochlaena palustris) Khas Kalimatan Terhadap Bakteri Propionibacterium acnes Secara In Vitro - Apriliyana, Nafisah Sofia; Su'aida, Nily; Fadillah, Aris; Abdi, Muhammad; Azkya, Nurizka; Nadiati, Nadiati; Halimah, Siti (Universitas Borneo Lestari, 2025)
Several acne therapy modalities have been widely used to eradicate Propionibacterium acnes, the causative pathogen of acne. However, it cannot treat acne optimally and has adverse effects. Kelakai (Stenochlaena palustris) possesses antibacterial activity. Based on the antibacterial activity of S. palustris, its leaf can be utilized as an alternative acne therapeutic substance. Therefore, this study investigated the effects of the ethanol extract of S. palustris leaf on P. acnes. The extraction of S. palustris was performed using maceration with 96% ethanol. The antibiotic activity test was divided into five groups: a positive control group (Clindamycin), a negative control group (Propionibacterium acnesATCC®6919), and three test groups with concentration gradients. Phytochemical analysis was positive for the identification of saponins, tannins, alkaloids, steroids and flavonoids. The inhibitory diameter of P. acnes at 75% extraction concentration was closest to that of the positive control group and has inhibition zone of diameter 13,99 + 0,77 (strong inhibition) indicating its effectiveness in inhibiting the growth of P. acnes. Based on the antibacterial activity of the ethanol extract of S. palustris leaf, the leaf extract has the potential to be used as a medicinal substance in acne therapy.